Electromagnetic wave scatteringin vegetal coverage’s (2010)
In this work one presents a study of the interaction of the electromagnetic waves with caduceus and coniferous leaves in the microwaves lengths, by means of the electrodynamics scattering theory. It begins with a brief explanation of the basic concepts of remote sensing, followed by the study of the dielectric mixture theory in vegetative materials and it finishes with the mathematical development of Helmholtz’s Integral equation, which relates the scattered field of the distant zone, with the field induced on a vegetative scatterer.